Incompleteness of Norms Regarding the Deadline for Cancellation of Certificates Above 5 Years in the Context of Land Law Certainty - Ari Yuliani, Anggi; Herlindah; Hamidi Masykur, Mohammad (Faculty of Law, Universitas Pekalongan, 2025)
The government has clearly stated the purpose of land registration through the Basic Agrarian Law. This law applies to all regions in Indonesia. It ensures legal certainty for the community. Article 19, paragraph (1) clearly states this. The following articles regulate the stages prior to the issuance of certificates. First, the land area is measured. Then, a map is created in printed form. Once the mapping stage is complete, the data is recorded in a register. The land registration system is inadequate. This has led to overlapping land ownership and procedural errors in land registration. As a result, there are administrative defects in land certificates. These administrative defects can render certificates invalid. Land disputes are common and take a long time to resolve, particularly those related to the invalidation of certificates that have been invalid for more than five years. The application and implementation of policies for resolving these disputes lack complete regulations or have incomplete legal norms. This leads to legal uncertainty in the resolution and ownership of the land